STRATEGI PENGEMBANGAN AGRIBISNIS JAMBU GONDANG MANIS (Syzygium malances ) DI KABUPATEN JOMBANG - Agus Suhadi; Sumarji Sumarji; Ahsin Daroini (Universitas Islam Kadiri, 2019)
Jombang district is one producing quality products which have been the malay apple Gondang Manis be forced out o Minister of Agriculture Indonesian decree number 308: / kpts / sr.120 / 4 / 2006 about the release of malay apple Gondang Sweet be forced out Gondang Sweet as a superior varieties.Malay Apple Gondang Manis it has good potential economic viewed from the side , with just over 10 years have fruit , we can get good thing around .2.000.000 rupias up to .With harvest 3.000.000 3 times a year .An apparition fruit with the color of a blackish color purplee ( interesting , the skin of shiny and smooth if fruit was an old man , with a sweet taste fresh , with color daing white as cotton and fruit with fragrant smell .Malay apple Gondang Sweet be forced out o is Sweet Gondang village in district Jombang ,kedung mulyo Sub district. The purpose of this research is to identify the factors what effect and the best strategy in the development of cashew gondang sweet, agribusiness for the location of the study in the village Gondang Sweet subdistrict Bandar Kedungmulyo, Jombang. District.This research was conducted over ( 3 ) months and the other months april to june 2019.The data used in this research is primary data and secondary data.The primary data are just data taken directly from the research site in the village gondang sweet, through direct observation on the scene, an interview with the government, the store, society and charging kuisoner.Respondents were 15 people to fill kuisoner research as follows: ( 2 ), the government that is the desadan, device dept of agriculture employees jombang ( 1 people ) community shop ( 2 people ), the main culprit ( 8 people ), and podarwis ( 2) people. Secondary database is the databas on obtained through the institutions in this study , good tabulation and deskriptif.metode the analysis SWOT by QSPM analysis . Based on the research and discussion , so it can be concluded that alternative development strategy agribusiness malay apple Gondang Sweet proper is the agribusiness development strategy so rosy Gondang sweetened with the intersection between agroekologi gondang sweet in the human resources which are in accordance with good quality , adoption of technology to produce superior , can bear fruit outside the others and the keep malay apple Gondang Sweet .nilai attraction highest on strategic 1 ( so ) by the total number of attraction of 6,85 ) ( bag . By doing action between local governments , a leading perpetrator of , community leaders , bumdes each other fused to produce malay apple Gondang Sweet excelling both in quality and quantity , protect the peculiarities of malay apple Sweet Gondang has already dispersed by minister of agriculture with potential ways to improve the preservation cashew gondang sweet is as typical owned by village Gondang Sweet subdistrict, Jombang district.